Underlying Social Attitudes Towards Conservation of Threatened Carnivores in Human-Dominated Landscapes - Zorondo-Rodriguez, F (Cambridge University Press, 2020)
Carnivore conservation depends on people s willingness to implement management practices to reduce threats to carnivores and mitigate conflicts between carnivores and domestic animals. We assessed the willingness of rural communities in central-southern Chile to (1) conserve carnivores, and (2) adopt management practices to reduce predation of domestic animals, a key factor triggering carnivore-human conflicts in rural areas. The study focused on five carnivores: The chilla Lycalopex griseus, the culpeo Lycalopex culpaeus, Darwin s fox Lycalopex fulvipes, the guiña or kodkod Leopardus guigna, and the puma Puma concolor. We found that rural communities perceived that threats towards carnivores rarely occurr in their region, contrary to the literature on this subject; people s attitudes differed depending on the carnivore; and people were willing to adopt management practices to help conserve carnivores (e.g. overnight protection of domestic animals and investment in infrastructure for henhouses and cowsheds), except leashing dogs. The willingness to conserve carnivores and adopt practices that would help do so may be associated with how these measures affect people s well-being. Although rural communities would like carnivores to be conserved, this cannot be achieved unless some pivotal practices, such as management of domestic dogs, are adopted by these communities. For successful biodiversity conservation outcomes in human-dominated landscapes, the social incentives necessary for rural communities to adopt appropriate management practices must be identified and implemented. © 2019 Fauna & Flora International.